Analisis Kebutuhan Pengembangan E-Modul Berbasis Imtaq Pada Pembelajaran Biologi Di Sma Negeri 11 Pekanbaru - Novita Ayu Novriandini; Siti Robiah; Nurkhairo Hidayati (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the needs of teachers and students regarding the development of IMTAQ-based e-modules in Biology learning at SMA Negeri 11 Pekanbaru. This study used a mixed methods method with a sequential exploratory design, which began with qualitative data collection through interviews and observations, then continued with quantitative data collection using questionnaires. The research subjects included one Biology teacher and 30 grade XI students. The interview results showed that teachers needed systematic, interactive, and integrated IMTAQ value teaching materials because the learning media used did not fully support the strengthening of spiritual aspects. The results of the student questionnaire showed that all need indicators were in the needed category, including the need for interactive teaching materials (73%), integration of IMTAQ values (69%), student readiness to use digital e-modules (79%), and expectations for IMTAQ-based e-modules (80%). The results of this study indicate that IMTAQ-based e-modules are very relevant to be developed as Biology learning media that support conceptual understanding while fostering students' character values.